2012
DOI: 10.1371/journal.pone.0034366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in HPV-Driven Viral Carcinogenesis: Redox Proteomics Analysis of HPV-16 Dysplastic and Neoplastic Tissues

Abstract: Genital infection by high risk Human Papillomavirus (HR-HPV), although recognized as the main etio-pathogenetic factor of cervical cancer, is not per se sufficient to induce tumour development. Oxidative stress (OS) represents an interesting and under-explored candidate as a promoting factor in HPV-initiated carcinogenesis. To gain insight into the role of OS in cervical cancer, HPV-16 positive tissues were collected from patients with invasive squamous cervical carcinoma, from patients with High Grade dysplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 50 publications
6
71
1
Order By: Relevance
“…28,29 In addition, redox proteomics identified the differential expression of ERp57, GST, TrxR2, and iNOS as a biomarker profile for HPV-positive invasive cervical carcinoma. 30 However, HPV genotyping was often not performed or considered in previous proteomics studies of cervical carcinoma. In our study, the protein expression pattern of HPV16-positive tumor specimens was compared with that of HPV-negative NC from the uterine cervix by 8-plex iTRAQ proteomics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 In addition, redox proteomics identified the differential expression of ERp57, GST, TrxR2, and iNOS as a biomarker profile for HPV-positive invasive cervical carcinoma. 30 However, HPV genotyping was often not performed or considered in previous proteomics studies of cervical carcinoma. In our study, the protein expression pattern of HPV16-positive tumor specimens was compared with that of HPV-negative NC from the uterine cervix by 8-plex iTRAQ proteomics.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 CRNN is a marker of late epidermal differentiation and is downregulated in cervical lesions. 25,30 FBN/LTPB is a calcium-binding protein of the extracellular matrix, and overexpression of FBN2 but not FBN1 has been reported in cervical adenocarcinoma. 40 LUM is a small leucine-rich proteoglycan expressed in the periphery of cancer nests of cervical SCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been linked to DNA repair as a member of the damage recognition complex and as a potential regulator that binds to genes with recognized repair functions (Chichiarelli et al, 2007). Several studies have linked PDIs to different types of cancer, including gastric (Leys et al, 2007), prostate (Pressinotti et al, 2009), esophageal (Ayshamgul et al, 2011), cervical (De Marco et al, 2012;Chung et al, 2013), salivary gland (Müller et al, 2013), bone metastasis (Santana-Codina et al, 2013), and breast (Lee et al, 2012;Gaucci et al, 2013) cancers. Another gene in this superfamily, PDIA6, also encodes a product that exhibits chaperone activity by inhibiting misformed protein aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The progression from mild dysplasia to severe dysplasia, and onwards to invasive cancer, is promoted by increasing levels of oxidative stress (27,28). Proteomics analysis of HPV-16 infected tissues have indicated that dysplasia is characterized by an increased oxidative environment compared to normal or neoplastic tissue, resulting in the oxidative modification of DNA and proteins involved in cell morphogenesis and terminal differentiation, thus providing ideal conditions for disease progression and cancer (28). The use of antioxidants including ellagic acid and Annona muricata may counterbalance the damaging effects of oxidative stress by arresting the cell cycle, promoting DNA repair and inducing apoptosis, thus hampering disease progression.…”
Section: Discussionmentioning
confidence: 99%